DATA SECURITY IN COMPUTERS: AN INTRODUCTION TO THE CONCEPT OF ENCRYPTION - Loso Judijanto; Al-Amin (ADISAM Publisher, 2025)
Encryption is a vital process in computer data security that converts open information into encrypted text to protect it from unauthorised access. The process relies on the use of complex algorithms and decryption keys that ensure that only authorised parties can access the information. Encryption security is crucial in this digital age to maintain privacy and protect the information assets of organisations and individuals during data storage and transmission. However, the implementation of this security faces challenges such as secure key management, selection of robust and efficient algorithms, and complying with regulations related to the use of encryption technology. With continuous development and multi-stakeholder engagement, encryption-based data security can be continuously strengthened to deal with dynamic cyber threats.